Valorization of animal bone into phosphorus biofertilizer: effects of animal species, thermal processing method, and production temperature on phosphorus availability. Issue 4 (4th July 2021) - Ahmed, Milkiyas; Nigussie, Abebe; Addisu, Solomon; Belay, Berhanu; Sato, Shinjiro
ABSTRACT: Thermal processing has been promoted to recycle phosphorus (P) contained within animal bone. There is a dearth of information on the mechanisms that control P solubility and availability from thermally treated bones. Chemical extraction, XRD, and FTIR were used to elucidate P solubility, and incubation and pot experiments to evaluate P bioavailability from different animal bones, thermal processing methods (pyrolysis vs. combustion), and production temperatures. Pyrolysis resulted in higher formic P than combustion, particularly at temperatures >500°C. Chicken bone showed the highest water-soluble P content ( p < 0.001), irrespective of processing methods and temperatures. In contrast, pig bone exhibited the lowest water-soluble P despite its high total P content. The XRD and FTIR studies confirmed higher degree of crystallization for those produced from pig bone, combustion, and higher temperatures (>700°C). Infrared splitting factor and width at 85% of the height of the 604 cm −1 peak were used to assess bioapatite crystallinity, and confirmed a negative correlation between crystallinity and P availability ( p < 0.001), indicating the attribution of bioapatite crystallization for low soluble P during combustion and higher temperatures. In low pH soil (pH~4), the addition of thermally treated bones increased Olsen-P and plant P uptake by two- to five-folds compared with unamended soils; however, no significant variation was observed in higher pH soil (pH~7). The finding suggested processing bones below temperatures of 700°C resulted in less crystallinity, thus higher P solubility. The P-fertilizing value of thermally treated bones was more pronounced in lower pH soil.